SESAMOL IN ASSOCIATION WITH FOLIC ACID SHOWS ANTI-PARKINSON EFFECT ON 6-OHDA INDUCED PARKINSONIAN ANIMAL BY REGULATING THE PARK GENES - KHADIRA SEREEN A,; VIJAYALAKSHMI K, (International Journal of Pharma and Bio Sciences, 2015)
Parkinson disease (PD) is a progressive neurodegenerative disorder which leads to motor impairment. Sesamol (SA) is a potent antioxidant, present in sesame oil and Folic acid (FA) involved in dopamine synthesis was combined together in this study and their impact on 6-OHDA induced animals was to be studied. The gene and protein expression of DJ-1, LRRK-2 and parkin were analysed by RT-PCR and western blotting. The level of dopamine was estimated by fluorimetric analysis. The presence of tyrosine hydroxylase positive (TH+) neurons was analysed by immunohistochemistry. On comparison with L-dopa, the SA and FA treated animals shows a protective effect on neurons toxicated with 6-OHDA. SA and FA suppress LRRK-2 and trigger the DJ-1 and parkin synthesis by regulating their respective gene. SA and FA have regulated dopamine level and TH+ neurons. Thus SA and FA may serve as a novel combined drug for treatment of PD.